High-frequency ultrasound characterization of vulvar skin in patients with lichenoid vulvar dermatoses and correlation of its vascular index with microvessel density and microvessel area - Chen, Jiyun; Shen, Kaikai; Xv, Jun; Shi, Yujie; Liu, Qiuyu; Zhu, Haohui; Zhang, Xijun (Frontiers in Medicine, 2026)
ObjectivesWe utilized high-frequency ultrasound to characterize vulvar skin alterations in lichenoid vulvar dermatoses (LVD) and to determine whether the sonographic vascular index (VI) correlates with histopathological microvessel density (MVD) and microvessel area (MVA).MethodsThis study included thirty-seven patients with pathologically confirmed LVD who attended Henan Provincial People’s Hospital between December 2021 and May 2024. A control group of thirty-five healthy women, matched for age and BMI was selected during the same period. High-frequency ultrasound parameters of the vulvar skin between the two groups were analyzed using statistical tests. Vulvar skin specimens from LVD patients were stained with CD34 to determine MVD and MVA, and the correlation with the VI from ultrasound parameters was assessed.Results(i) Analysis of variance showed that epidermal thickness, subepidermal low echogenic band (SLEB) thickness, dermal thickness, and VI were significantly increased in the LVD group compared to the control group (all P < 0.05). (ii) Correlation analysis revealed a positive correlation between the VI and MVD, MVA (r = 0.438, r = 0.630, both P < 0.05).ConclusionThe vulvar skin thickness and VI in patients with LVD are increased compared to the control group. The VI reflects the microvascular status in LVD, highlighting the significant value of high-frequency ultrasound in assessing LVD.